Penempatan SDM Penyandang Disabilitas di Sektor Pariwisata - Kartika, Titing; Yuniarsih, Tjutju; Hadijah, Hady Siti (Jurnal Master Pariwisata (JUMPA), 2021)
The existence of a negative stigma in society’s view for persons with disabilities makes them unable to show their optimal self-existence even though they competently have them. Not all industries or government agencies have implemented the rules whereby the agencies they manage should implement rules for employing persons with disabilities (the proportion is private sector 1 %, and government agencies 2%) referring to the rules mandated in Law no. 8 of 2016 concerning Persons with Disabilities. According to the perspective of Human Resources management, this is a challenge how the existence of persons with disabilities can get space without discrimination from all parties. The resultsof research showed that the inoptimal placement of human resources with disabilities occurred due to several factors, both from the person and the employer. The involvement of stakeholders has an important role in solving problems from associations, universities, communities and the government. Keywords: Disabilities, Human Resources, Tourism Sector, Employee Placement